Pengaruh Struktur Modal, Struktur Aset dan Profitabilitas terhadap Potensi Terjadinya Financial Distress Perusahaan (Studi pada Perusahaan Manufaktur Sektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Periode 2014-2017) - Alien Akmalia (Business Management Analysis Journal (BMAJ), 2020)
The purpose of this study is to examine the effect of capital structure proxied by Financial Leverage and Equity Structure, Asset Structure and Profitability to the potential for Financial Distress in the company. The sample used in this study is various industrial sector manufacturing companies listed on the Indonesia Stock Exchange during the period 2014 to 2017. The sample selection method used was the purposive sampling method. Hypothesis testing is done using logistic regression. Based on the results of hypothesis testing it can be concluded that the financial leverage variable is proven to have a significant positive effect on the likelihood of financial distress, the Asset Structure Variable is proven to have a significant negative effect on the likelihood of financial distress, as well as the Return on Asset variable also has a significant negative effect on the likelihood of financial distress . While the Equity Structure variable was not proven significant in influencing the likelihood of financial distress in the company.